1992
DOI: 10.1007/bf02925896
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cadmium and nickel on ethylene biosynthesis in soybean

Abstract: Exogenously supplied cadmium and nickel considerably affected the ethylene biosynthesis in soybean cuttings. Cadmium stimulated ethylene production by increasing production of free ACC and stimulating EFE activity. Nickel inhibited ethylene production by depressing EFE activity, but stimulated the production of free ACC. Both heavy metals did not apparently affect cell membrane integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…However, the presence of ACCD may obscure siderophore‐related effects. Based on the observation that S. tendae F4 does not show ACCD activity, we speculate that the bacterium, though a siderophore and an auxin producer, could not clearly enhance plant growth, probably, because of the occurrence of high levels of stress ethylene induced by Cd (Pennasio and Roggero 1992), which, in this case, might not have been neutralized owing to the absence of a bacterial ACCD. Possibly, the amount of siderophores produced in soil might have been insufficient to counter the inhibitory effect of Cd on auxins, which seemed apparent from the fact that most of the siderophores were involved in plant Fe uptake – hence higher Fe content in these plants – rather than in interacting with Cd.…”
Section: Discussionmentioning
confidence: 92%
“…However, the presence of ACCD may obscure siderophore‐related effects. Based on the observation that S. tendae F4 does not show ACCD activity, we speculate that the bacterium, though a siderophore and an auxin producer, could not clearly enhance plant growth, probably, because of the occurrence of high levels of stress ethylene induced by Cd (Pennasio and Roggero 1992), which, in this case, might not have been neutralized owing to the absence of a bacterial ACCD. Possibly, the amount of siderophores produced in soil might have been insufficient to counter the inhibitory effect of Cd on auxins, which seemed apparent from the fact that most of the siderophores were involved in plant Fe uptake – hence higher Fe content in these plants – rather than in interacting with Cd.…”
Section: Discussionmentioning
confidence: 92%
“…Soil contaminated by heavy metals is absorbed by the roots of the plant and diffused to the different parts of plants, which consequently disturbs the plant's metabolic activity as well as deteriorate the plant development [269,270]. When plants are exposed to heavy metal stress or other abiotic stresses the endogenous ethylene level increases [259,[271][272][273]. Pseudomonas koreensis AGB-1 isolated from Miscanthus sinensis is effective against metal toxicity and contains heavy metal marker genes in their genome [274].…”
Section: Heavy Metal Stressmentioning
confidence: 99%
“…Doelman (1985) has reported that the efficiency of revegetation and phytoremediation of heavy metal-contaminated sites is closely related to the presence of higher proportions of metal resistant microbial populations in the soil, which likely conferred a better nutritional assimilation and protection effect on plants. It is known that contamination of soil with heavy metals increases the accumulation of ACC and ethylene in plant roots (Pennasio and Roggero, 1992). It may be speculated that increased accumulation of ACC in roots, caused by stressful growth conditions, can facilitate colonization of the rhizoplane with some metal-resistant forms of ACC-utilizing bacteria to some extent by providing the bacteria with additional sources of nitrogen, such as ACC.…”
Section: Plant Growth Promoting Potential Of a Xylosoxidans Ax10mentioning
confidence: 99%